Mothers Breastfeeding Knowledge About Relationship With The Benefit Of Giving Asi Asi In Exclusive In The District Jombang - Wahyu Anjas Sari; Gempi Tri Sumini (Universitas STRADA Indonesia, 2020)
Exclusive breastfeeding is breastfeeding without additional food and other beverages in infants aged 0-6 months (Forum, 2017). Milk given to infants because of the many benefits and advantages, such as infants have protection against Clostridium tetani bacteria, diphtheria, polio virus, rotavirus and vibrio colera. Moreover, it can increase the child's IQ and EQ (Hubertin, 2014). The issues raised is whether there is a relationship between knowledge about the benefits of breastfeeding to exclusive breastfeeding. The goal is to determine the relationship between knowledge about the benefits of breastfeeding to exclusive breastfeeding in nursing mothers. Population was all nursing mothers in the Village District Gondek Mojowarno Jombang district as many as 94. Sampling purposive sampling technique. The sample in this study that met inclusion and exclusion criteria are as many as 48 people. The study design was cross-sectional correlation with the approach and the data were collected using a questionnaire, and analyzed using chi square test statistic. The results of knowledge about the benefits of breastfeeding to exclusive breastfeeding in nursing mothers is good knowledge, exclusive breastfeeding as much (4.2%), does not give exclusive breastfeeding as much (4.2%) while the knowledge enough mother, exclusive breastfeeding (22.9%), not giving (27.1%) and mothers who know less, exclusive breastfeeding (4.2%), not exclusively breastfed (37.5%). From the results of statistical tests obtained X2 = 7234 (7234> 5.591). This suggests there is a relationship between knowledge about the benefits of breastfeeding to exclusive breastfeeding in nursing mothers. The conclusion is there hubunagn between knowledge about the benefits of exclusive breast feeding with breast milk in nursing mothers in the Village District Gondek Mojowarno Jombang District. Proposed research is expected to come keposyandu diligent mothers or other associations to get information about health and are expected to give exclusive breastfeeding if the mother had another baby, for health care workers should routinely provide information and motivate breastfeeding mothers to breastfeed exclusively